Analisis Pengaruh Kebebasan Ekonomi dan Politik terhadap Pertumbuhan Ekonomi Delapan Negara ASEAN Periode 1997 - 2007 - Laksono, Riandy (UI Scholars Hub, 2010)
Economic and political systems might have a great share in determining the speed of the economic growth in an economy. Majority of the researchs in the past relied on physical input accumulation in determining economic growth, without taking into account the contribution of institutional characteristics. This research is aimed to test the hypothesis that economic freedom and political system affect the economic growth. Using panel data method (pooled least square approach) in eight ASEAN countries during the perioo of 1997-2007 and based on a framework of Solow economic growth model, it is showed that the more free and efficient economy leads to faster economic growth, and political democracy can otherwise hinder economic growth. Economy can grow higher if public policies are directed to the creation of a stable monetary conditions, a more efficient in intermediation of financial markets, approp1iate public budget policy, straightforward and efficient regulations, corruption eradication, as well as lower taxes. Nevertheless the index of investment freedom and property rights are far away from the behaviors of existing theories and hypothesis, so further research is needed.